Understanding the Diverse and Essential Roles in Contemporary Healthcare Systems - Tariq Saeed Saleh Al-Ghamdi; Maha Saad Ali Haydan; Naif Mohammed Alsidrah; Maha Raki Alruwaili; Afrah Habis Faleh Alshammari; Abdulrhman Saad Alqahtani; Khalid Mohammed Abdu Madkhali; Ghaith Saleh Alharbi; Rafat Hussam Abushanab; Yahya Ahmed Mater Mahzari; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare systems today are complex and dynamic networks requiring the collaboration of diverse professionals, each bringing specialized skills to improve patient outcomes. These systems cater to a wide range of needs, from disease prevention and diagnosis to treatment and rehabilitation. The roles within healthcare have evolved significantly, driven by advancements in technology, medical research, and the growing complexity of patient care. This review explores the contributions of various healthcare specializations, ranging from general physicians who provide holistic, primary care to preventive medicine specialists who focus on health promotion and disease prevention. Additionally, the roles of nursing specialists, physical therapists, clinical laboratory scientists, medical device experts, and more are highlighted, demonstrating their collective impact on modern healthcare delivery. Understanding these roles is essential to appreciating the collaborative framework that ensures efficient, patient-centered care in contemporary healthcare systems.